Extensions of r12 corrections to CC2-R12 for excited states - Neiß, Christian; et al. (Journal of Chemical Physics, 2006)
As known since about two decades, R12 methods, which include terms linear in the interelectronic distance r in the wave function, improve substantially the basis set convergence of the ground state correlation energy. In a previous study, however, it was found that the same approach does not give a similar systematic improvement if applied to excited states in the framework of coupled cluster response theory. In the present work, we examine the reason for this behavior and show that the inclusion of additional orbitals in the construction of the r pair functions leads to an enhanced basis set convergence (and thus a balanced description) also for the excited states. © 2006 American Institute of Physics.